2009
DOI: 10.1088/0004-637x/703/2/1964
|View full text |Cite
|
Sign up to set email alerts
|

Disk Evolution in the Three Nearby Star-Forming Regions of Taurus, Chamaeleon, and Ophiuchus

Abstract: We analyze samples of Spitzer Infrared Spectrograph spectra of T Tauri stars in the Ophiuchus, Taurus, and Chamaeleon I star-forming regions, whose median ages lie in the <1-2 Myr range. The median mid-infrared spectra of objects in these three regions are similar in shape, suggesting, on average, similar disk structures. When normalized to the same stellar luminosity, the medians follow each other closely, implying comparable mid-infrared excess emission from the circumstellar disks. We use the spectral index… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
251
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(271 citation statements)
references
References 132 publications
20
251
0
Order By: Relevance
“…From the remaining 289 listed targets, 156 members have assigned spectral types from optical and/or near-IR spectroscopy and evidence of youth (please see the review for references), while 133 did not have any spectral type assigned at that time; - Cieza et al (2010) derived spectral types for a total of 34 sources, nine of these had previously determined spectral types, while the remaining 25 sources are located outside the central region of the cluster and were therefore not included in our compilation; -Alves de Oliveira et al (2010) computed spectral types for six new brown dwarfs and one very low mass star; - McClure et al (2010) determined spectral types for a few tenths of sources and their binary components (from which 9 are shown in Table 5), including 25 candidate members compiled by Wilking et al (2008) which lacked spectroscopic and four sources that were not part of that list but have spectral types and membership determined in the literature. N.B., some of these spectral types had been published earlier by Furlan et al (2009), though it is in this paper that the data reduction and analysis are presented; - Geers et al (2011) derived the spectral type for one new brown dwarf; - Erickson et al (2011) confirmed 30 new members with optical spectral types, where only three were part of the Wilking et al (2008) compilation. They combined all the new members with 88 previously known members with optical spectral type from an analogous optical survey (Wilking et al 2005), 14 members compiled from the literature, and three members for which they presented optical spectral types but had already near-IR spectral types determined by Luhman & Rieke (1999); -in this work we confirm spectroscopically three new members with spectral types indicative of masses above the substellar limit (besides the 13 brown dwarfs already included in Table 5, and the four members with uncertain spectral types that we do not include in this analysis); totalling a list of 250 members of the cluster where 208 have spectral types earlier than M6, and 42 have spectral types later than or equal to M6.…”
Section: The Cluster's Stellar Populationmentioning
confidence: 93%
See 1 more Smart Citation
“…From the remaining 289 listed targets, 156 members have assigned spectral types from optical and/or near-IR spectroscopy and evidence of youth (please see the review for references), while 133 did not have any spectral type assigned at that time; - Cieza et al (2010) derived spectral types for a total of 34 sources, nine of these had previously determined spectral types, while the remaining 25 sources are located outside the central region of the cluster and were therefore not included in our compilation; -Alves de Oliveira et al (2010) computed spectral types for six new brown dwarfs and one very low mass star; - McClure et al (2010) determined spectral types for a few tenths of sources and their binary components (from which 9 are shown in Table 5), including 25 candidate members compiled by Wilking et al (2008) which lacked spectroscopic and four sources that were not part of that list but have spectral types and membership determined in the literature. N.B., some of these spectral types had been published earlier by Furlan et al (2009), though it is in this paper that the data reduction and analysis are presented; - Geers et al (2011) derived the spectral type for one new brown dwarf; - Erickson et al (2011) confirmed 30 new members with optical spectral types, where only three were part of the Wilking et al (2008) compilation. They combined all the new members with 88 previously known members with optical spectral type from an analogous optical survey (Wilking et al 2005), 14 members compiled from the literature, and three members for which they presented optical spectral types but had already near-IR spectral types determined by Luhman & Rieke (1999); -in this work we confirm spectroscopically three new members with spectral types indicative of masses above the substellar limit (besides the 13 brown dwarfs already included in Table 5, and the four members with uncertain spectral types that we do not include in this analysis); totalling a list of 250 members of the cluster where 208 have spectral types earlier than M6, and 42 have spectral types later than or equal to M6.…”
Section: The Cluster's Stellar Populationmentioning
confidence: 93%
“…The disk population of the ρ Ophiuchi cluster has been studied in great detail (e.g., Natta et al 2002;Andrews & Williams 2007;Furlan et al 2009;Andrews et al 2010;Ricci et al 2010;Cieza et al 2010;McClure et al 2010). It is found that, despite the young age of the cluster (∼1 Myr), many circumstellar disks in ρ Oph are evolved showing features such as millimeter size dust grains in the outer disk region (Furlan et al 2009;Andrews et al 2010;Ricci et al 2010), inner opacity holes characteristic of transition disks (Cieza et al 2010), dust settling, and dust grain processing (e.g., McClure et al 2010).…”
Section: Slopes Of the Spectral Energy Distributionsmentioning
confidence: 99%
“…To survey the innermost regions of TD objects for stellar companions, we collected multi-epoch, high-resolution optical spectroscopy of 24 stars in Oph identified as having TDs (C10; Andrews & Williams 2007a;Geers et al 2007;Furlan et al 2009), two in Corona Australis (CrA; <3 Myr; Neuhauser & Forbrich 2008;Sicilia-Aguilar et al 2008;Hughes et al 2010 .5 ensures that all of the targets have significant mid-IR excesses at 24 μm. We included an additional four Oph targets and seven from other regions, all of which were identified by other authors using the same criteria as C10 (Andrews & Williams 2007a;Geers et al 2007;Furlan et al 2009).…”
Section: Sample and Observationsmentioning
confidence: 99%
“…We included an additional four Oph targets and seven from other regions, all of which were identified by other authors using the same criteria as C10 (Andrews & Williams 2007a;Geers et al 2007;Furlan et al 2009). …”
Section: Sample and Observationsmentioning
confidence: 99%
See 1 more Smart Citation